Sporadic Intra-Abdominal Desmoid: A Rare Presentation as a Hepatic Mass. (4th October 2012) - Gupta, Shahana; Ray, Udipta; Chatterjee, Souvik; Kumar, Sanjeev; Satapathy, Ayusman; Chatterjee, Shamita; Choudhury, Tamal Kanti
Abstract : We report an unusual presentation of a sporadic intra-abdominal desmoid tumour, possibly arising from the diaphragm, masquerading as a hepatic mass in a young female without any history of surgery or trauma. Histopathology ruled out a hepatic origin of the tumour as was inferred from pre- and intraoperative evaluation. Immunohistochemistry showed positivity of lesional fibroblastic cells for β -catenin and negativity for CD34, CD117, EMA, SMA, desmin, vimentin, cytokeratin, and ALK1 thereby confirming the diagnosis of a desmoid tumour. There exist only a few reports in the literature on desmoids related to the diaphragm, but only one on a diaphragmatic desmoid that is possibly primary.